دور الموازنة المرنة على أساس النشاط في الرقابة على التكاليف (دراسة تطبيقية في الشركة العامة للصناعات الجلدية) - العبيدي, صبيحة برزان (Journal of Economics and Administrative Sciences, 2009)
The research aims to identify the level of increase or decrease the product cost through the activity based flexible budgeting that gives us the chance to follows the cost since the product is planed to be made till it appears in the market and it also helps to fined out any problems that are expected to happen in the future and to put the costs under control, also to know much the surveying affects the perfect use for the complete resources in order to be used in the demanded way, the research is divided in to three sides ,the first is specialized for the theoretical side, the second is for the partical side, while the third side is specialized for the conclusions and recommendations.